(untitled) (Damascus University Journal of arts and humanities sciences, 2025)
The research examined natural characteristics, which included geological formations dating back to the fourth which go back. The ancient climate had an important role to play, particularly in rainfall periods that increased aquatic erosion activity and helped to build many valleys in the far north-east of the river, which are nutritious areas as a result of sloping torrents. (The valleys are Jalat, Alabeeter, Qarat Tiba, Khoysa, Abu-West South, Jifta) The current climate has led to warmer temperatures and increased evaporation during the summer. Most of the country’s land has been drained. The water of the ponies has been lost through the smuggling of Ali West in the winter. The soil has shown the results of the analysis of qualitative characteristics to the high proportion of salts and wards. The watercourse has a positive effect of protecting Ali West from flooding as well as reserving the water of the ponies. The research examined the morphometric characteristics of the pontifical valleys and included the formal, geometric, topographic and water network characteristics of the GIS programme. (GIS) and digital height model (DEM) quantitative analysis results have shown that all valleys tend to have rectangular shape.